A text mining analysis of European banks' and insurers' disclosures on climate-related risks - Anna Kraus (Risk Management and Insurance Review, 2024)
This paper empirically analyzes sustainability-related disclosures of listed European banks and insurance companies by focusing on transition risks, physical risks as well as stranded assets as a possible consequence of transition and physical risks. We employ a text mining analysis and apply a comprehensive keyword catalog to 142 firms. The dataset used for the analysis comprises 852 annual and 551 sustainability reports, covering a sample period from 2017 to 2022. Our results show that disclosure on climate-related risks considerably increases over the examined period, but that reporting on stranded assets is still in early stages. Moreover, European insurers report more on climate-related risks relative to the number of analyzed tokens than banks. Finally, statistical evidence suggests that larger banks and insurers with above-median market capitalization exhibit significantly more word hits on climate-related risks as compared to smaller firms.
Keywords: 330